Mechanisms of Sudden Cardiac Death: Oxidants and Metabolism - Yang, Kai-Chien (Circ Res, 2015)
Ventricular arrhythmia is the leading cause of sudden cardiac death (SCD). Deranged cardiac metabolism and abnormal redox state during cardiac diseases foment arrhythmogenic substrates through direct or indirect modulation of cardiac ion channel/transporter function. This review presents current evidence on the mechanisms linking metabolic derangement and excessive oxidative stress to ion channel/transporter dysfunction that predisposes to ventricular arrhythmias and SCD. As conventional anti-arrhythmic agents aiming at ion channels have proven challenging to use, targeting arrhythmogenic metabolic changes and redox imbalance may provide novel therapeutics to treat or prevent life-threatening arrhythmias and SCD.